2015
DOI: 10.3855/jidc.5627
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and virulence genes of extraintestinal pathogenic Escherichia coli from tropical estuary, south India

Abstract: Introduction: Escherichia coli strains can cause a variety of intestinal and extraintestinal diseases. Extraintestinal pathogenic E. coli (ExPEC) strains have the ability to cause severe extraintestinal infections. Multidrug resistance among ExPEC could complicate human infections. Methodology: Escherichia coli strains were isolated during the period of January 2010 to December 2012 from five different stations set at Cochin estuary. Susceptibility testing was determined by the disk-diffusion method using nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Extraintestinal pathogenic E. coli in tropical estuaries raises concerns on such bacteria getting disseminated via seafood (Sukumaran & Hatha, 2015). In our study, three isolates were found positive for virulence genes associated with ExPEC.…”
Section: Discussionmentioning
confidence: 99%
“…Extraintestinal pathogenic E. coli in tropical estuaries raises concerns on such bacteria getting disseminated via seafood (Sukumaran & Hatha, 2015). In our study, three isolates were found positive for virulence genes associated with ExPEC.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli strains belonging to groups A and B1 do not frequently cause extraintestinal infection. These strains which are not highly virulent, generally cause disease only in hosts that are immunocompromised, and could be pathogenic in healthy hosts only if they were to acquire su cient extraintestinal factors [28]. All 3 isolated in group B1 were kpsMTII, mH, papC and tratT positive.…”
Section: Discussionmentioning
confidence: 99%
“…Infections caused by antimicrobial-resistant microorganisms such as Staphylococcus aureus and Enterobacteriaceae (O'Gara 2017, Price et al 2017) increase hospitalization and mortality rates, as well as health care costs (Cosgrove andCarmeli 2003, de Kraker et al 2011). Pathogens carrying resistance genes to antibiotics of clinical relevance have been isolated from recreational and other surface waters worldwide (Arvanitidou et al 2001, Huijbers et al 2015, Leonard et al 2015, Sukumaran and Hatha 2015, Young et al 2016, though the significance of beaches as reservoirs for, and transmitters of, antibiotic resistance genes is not well understood (Allen et al 2010). These microorganisms, unlike FIB, can be directly associated with adverse human health outcomes, and have shown increases in resistance coinciding with temperature increases (MacFadden et al 2018).…”
Section: Contaminants Of Emerging Concernmentioning
confidence: 99%